Idiopathic pulmonary hemosiderosis: case report - Ferrari, Giesela F. [UNESP]; Fioretto, José R. [UNESP]; Alves, Adriano F. R. [UNESP]; Brandão, Gicélia S. [UNESP] (Jornal de Pediatria, 2000)
OBJECTIVE: To alert pediatricians about the possibillity of childhood Idiopathic Pulmonary Hemosiderosis, in cases of anemia associated with chronic lung disease. METHODS: This article documents a case of Idiopathic Pulmonary Hemosiderosis in a 6 year-old child, with histopathological documentation, and reviews it against published literature. RESULTS: A 6 year-old child with history of anemia and lung disease characterized by wheezing, recurrent pneumonia and digital clubbing was admitted to the hospital for investigation, where he suffered sudden respiratory failure and hemoptysis.He was submitted to a lung biopsy which showed a histopathological diagnosis compatible with pulmonary hemosiderosis. Therapy with high doses of corticosteroids was initiated with a good early response. After two and a half months of therapy he had a new bleeding episode, culminating in death. CONCLUSIONS: Idiopathic Pulmonary Hemosiderosis should be included as a possible diagnosis of children with anemia and chronic lung disease. This case is a good example.